PENGARUH KUALITAS PELAYANAN, CITRA TOKO, DAN SUASANA TOKO TERHADAP MINAT BELI KONSUMEN (SURVEY KONSUMEN PADA SB HOUSEWARE, BUKITTINGGI) - Hidayat, Ikhsan; Karneli, Okta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine how much influence the quality of service, store image, and the atmosphere of the store to consumer buying interest in the company SB Houseware Bukittinggi branch. Samples in this study were taken as many as 100 respondents and techniques used Sampling probability. the data in this study using survey methods through questionnaires filled by consumers. Data obtained from the results of the questionnaire and then processed to then tested by statistics memlalui SPSS program. The results of analysis using simple linear regression analysis, multiple linear regression analysis, determination test (R2), individual significance test (t test), and simultaneous significant test (Test F) so that it can be seen that service quality variables influence consumer buying interest variable, store image have an effect on consumer buying interest variable, shop atmosphere variable have an effect on consumer buying interest variable, and service quality variable, store image, store atmosphere influence simultaneously to consumer buying interest variable. The calculation results are known R Square is the coefficient of determination and obtained R Square value of 0.541. That is, the quality of service, store image, and the atmosphere of the store affects consumer buying interest by 54.1%.Keywords: Service Quality, Store Image, Store Atmosphere, and Buying Interest Konsumen